Chapter Per un progetto della pedagogia italiana - CORSI, Michele (Studies on Adult Learning and Education, 2022)
Pedagogy is still searching for its own identity and epistemological status. Especially in Italy, where the task of pedagogy, despite the efforts of many and numerous pedagogical colleagues, still has a marginal role, particularly in its political and transformative value. This is why it is important to return to pedagogy in its foundational elements, but especially to pedagogy as a promoter of critical reflexivity and concrete actions for the present and future of society and new generations. The essay reviews the most recent history of pedagogy and its Scientific Societies and opens up to the challenges of the contemporary world with confidence and respect for the high mandate facing the pedagogical reflexivity.